Theatre Talks as Micro-Democracy - Ejgod Hansen, Louise (Nordic Theatre Studies, 2018)
The article discusses and analyzes the democratic potential of theatre-going within the framework of cultural policy. Theoretically, the article is based on three different approaches: theatre research and the link between theatre and democracy, cultural policy research on the strategy of democratization of culture, and the democracy theory of James S. Fishkin. The analysis is based on the empirical material of thirty-one theatre talks carried out as part of an audience development project and focuses on four different aspects of the democratic potential of theatre: First, how the theatre talks gave the participants the opportunity to reflect on the experience and thus gain a better understanding of the theatrical event. Secondly, the importance of the social setting of the theatrical event, and thus of creating a safe framework for new theatre visitors. Thirdly, the article provides a critical approach to a target-oriented approach to audience development in which the content of the performance should be matched with certain audience segments. And fourth, the article points to an outcome of the experience related to the challenging of one’s own view point and thus expanding one’s horizon.